The Effect of Self-Love and Stress Coping on Battalion Soldiers’ Wives’ Resilience - Azahrah, Faradillah Ayu; Krismastuti, Lucia Vega Tri; Seftian, Maulana (Interdisciplinary Social Studies, 2022)
The wives of the Paskhas 461st Battalion Soldier will encounter difficult problems in life, but they must be able to overcome them. For this reason, the wives of the Paskhas Battalion Soldier must have faith in their ability to handle these challenges without harshly criticizing or judging herself if they make mistakes or fail. The purpose of this study is to examine the influence of self-compassion on resilience, the influence of coping stress on resilience, and the influence of self-compassion and coping on resilience. This study is quantitative.  The subjects in this study were the wives of the Soldiers of the 461st Battalion 461 Paskhas Jakarta with a total of 108 samples using the purposive sampling technique. This study used 3 measuring instrument scales, namely: the resilience measuring instrument scale, the self-compassion measuring instrument scale, and the stress coping measuring instrument scale. The results of this study show that there is significant confusion between self-compassion towards resilience with R Square = 0.451 with a signification of 0.000 < (p) = 0.05. There is a significant influence between coping on resilience with n = 0.578, Fcount = 55.58, Ftable = 0.009. There is a significant influence between self-compassion and coping stress on resilience with R-Square = 0.495 with a signification of 0.000 < (p) = 0.05.